2017
DOI: 10.1215/03616878-3766737
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Public Opinion—Does It Influence the Diffusion of ACA Decisions?

Abstract: We consider two ways that public opinion influenced the diffusion of ACA policy choices from 2010 through 2014. First, we consider the policy feedback mechanism, which suggests that policy decisions have spillover effects that influence opinions in other states; residents in the home state then influence the decisions of elected officials. We find that both gubernatorial ACA announcements and grant activity increased support for the ACA in nearby states. Consistent with our expectations, however, only gubernat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Such trade-offs in observability may apply not only to political elites but to the public as a whole. Pacheco and Maltby (2017) demonstrate how citizens in neighboring states take note of other governments' experiments and begin to demand change at home. They establish that the resulting shifts in public opinion in turn influence policy choices.…”
Section: The Role Of Policy Attributesmentioning
confidence: 95%
See 1 more Smart Citation
“…Such trade-offs in observability may apply not only to political elites but to the public as a whole. Pacheco and Maltby (2017) demonstrate how citizens in neighboring states take note of other governments' experiments and begin to demand change at home. They establish that the resulting shifts in public opinion in turn influence policy choices.…”
Section: The Role Of Policy Attributesmentioning
confidence: 95%
“…Given the polarized political climate, not every governor leapt to embrace the ACA, accept grant funding, and develop a state health exchange. Rather, some governors only came to that position following other states' actions and the public opinion shifts that arose in their own states as a result, as Pacheco and Maltby (2017) establish.…”
Section: The Conditions For Policy Diffusionmentioning
confidence: 99%
“…Last is the question of whether elite action, as opposed to rhetoric, can influence public opinion. One study of policy diffusion found that pro-ACA gubernatorial an- nouncements in one state increased public support for the ACA in nearby states, a pattern the authors term "policy spillover" (Pacheco and Maltby 2017).…”
Section: Political and Policy Responses To Aca Provisions In The Statesmentioning
confidence: 99%
“…Public opinion, meanwhile, can profoundly impact medical policy [23,24] and insurance benefits [25], and in the reproductive medicine field, where insurance coverage remains a controversial issue, public support may promote consequential change. Moreover, public opinion affects media coverage, which in turn influences what the public (including the transgender community) may see as viable options for their care.…”
Section: Introductionmentioning
confidence: 99%